Vulnerable Road Users or Vulnerable Transport Planning? - Khayesi, Meleckidzedeck (Frontiers in Sustainable Cities, 2020)
The concept of vulnerable road users is widely used in transport and road safety discourse. The concept refers to walkers or pedestrians and cyclists (bicyclists and motorcylists) who are easily injured and killed in a car-dominated road space. Who is really vulnerable: road users or transport planning? This paper subjects the concept of vulnerable road users to a critical analysis. It finds this concept wanting because research and practice show that the real vulnerability lies within transport planning that gives in to influences that are more focused on the needs of motorized transport. The paper proposes the concept of vulnerable transport planning to underscore the fact that transport planning often lacks inclusion and is influenced by forces that favour motor vehicles. This influence leads to omission and neglect of walkers, cyclists, children, persons living with disabilities, the elderly and highway-adjacent communities in transport and land-use planning. A focus on vulnerable transport planning directs research and practice to addressing the root cause of vulnerability rather than concentrating primarily on those affected by this vulnerability.